Insults and oral attack between Demosthenes and Aeschines (Minerva, 2019)
In the current paper the insults and attacks that Demosthenes and Aeschines address to one another in several speeches are analyzed. A pragmatic approach is adopted because in order to understand insults it is mandatory to start from the shared assumptions between speaker and hearer, to examine the cultural values of the society in which they are generated and to observe whether they use a vocabulary socially considered as offensive, rude, vulgar or not. Therefore insults are classified in different semantic fields: personal origin, upbringing and education, occupation, moral faults and socially condemned behaviour, religion, sex and physical and mental defects. Finally we go deeply into in the interpretation of some passages by these authors.
Keywords: insults; oratory; Demosthenes; Aeschines